Cytological diagnosis of acanthomatous ameloblastoma - Walke Vaishali (Journal of Cytology, 2008)
Ameloblastomas show wide morphological spectra and may pose diagnostic difficulties. Of the many types encountered, acanthomatous ameloblastoma is a rare variant that possesses distinctive features. To the best of our knowledge, there have been no previous reports on the cytology of acanthomatous ameloblastoma (AA). An elderly male presented with a radiolucent jaw swelling. Cytology smears showed combinations of basaloid cells with peripheral palisading, stellate cells as well as squamous cells in groups and in isolation. A diagnosis of acanthomatous ameloblastoma was made and subsequently confirmed on histology. Although AA is a rare jaw tumor, it possesses distinctive cytological features that permit confident preoperative cytodiagnosis.